Global Expansion of the Australian Biting Louse Heterodoxus spiniger Facilitated by Human Transport of Dog (Canis familiaris), and Implications for Prehistoric Cultural Interaction in Australasia. (4th May 2021) - Koungoulos, Loukas; Contos, Peter
ABSTRACT: For over a century, it has been pondered how the biting louse Heterodoxus spiniger, which evolved on the agile wallaby ( Macropus agilis ) in Australia/New Guinea, came to be found on domestic dogs ( Canis familiaris ) throughout much of the world. Various theories suggest that ancient transport of Australian dingoes ( Canis dingo ), or recent transport of domestic dogs or macropods are responsible for its global distribution. In this paper, we utilise reported museum specimens, entomological surveys and veterinary data to define an updated distribution of this notable ectoparasite, and explore the evidence for transport of its hosts that may be responsible for its dispersal. In the simplest scenario, H. spiniger first transferred from wallaby to dog in prehistoric New Guinea, probably through humans using dogs to hunt wallabies. If the further spread of this species preceded the global connections brought by European colonisation, dogs of Austronesian maritime cultures were the most likely vectors for its further dispersals into Asia, but it probably only arrived in the Americas following European settlement. As ancient specimens are unlikely to be recovered due to poor preservation conditions, a genomic approach should be pursued in further investigation of this species' history.